2022
DOI: 10.1021/acs.jmedchem.2c00840
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent and Selective Dopamine D4 Receptor Antagonists Potentially Useful for the Treatment of Glioblastoma

Abstract: To better understand the role of dopamine D 4 receptor (D 4 R) in glioblastoma (GBM), in the present paper, new ligands endowed with high affinity and selectivity for D 4 R were discovered starting from the brain penetrant and D 4 R selective lead compound 1-(3-(4-phenylpiperazin-1-yl)propyl)-3,4-dihydroquinolin-2(1 H )-one ( 6 ). In particular, the D 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…We note that some previous investigations that did not detect D 4 R-mediated arrestin recruitment used luciferase complementation (Forster et al, 2020) or fluorescence microscopy to assess redistribution of βarr2 to the plasma membrane (Spooren et al, 2010). On the other hand, some of the studies that did find evidence for such recruitment used PathHunter (Keck et al, 2019;Pirzer et al, 2019) or bioluminescent resonance energy transfer (BRET) approaches to monitor βarr2-D 4 R interactions (Sánchez-Soto et al, 2016;Lyu et al, 2019;Pavletić et al, 2022). Assay sensitivity would seem a likely explanation for these discrepancies.…”
Section: Discussionmentioning
confidence: 94%
“…We note that some previous investigations that did not detect D 4 R-mediated arrestin recruitment used luciferase complementation (Forster et al, 2020) or fluorescence microscopy to assess redistribution of βarr2 to the plasma membrane (Spooren et al, 2010). On the other hand, some of the studies that did find evidence for such recruitment used PathHunter (Keck et al, 2019;Pirzer et al, 2019) or bioluminescent resonance energy transfer (BRET) approaches to monitor βarr2-D 4 R interactions (Sánchez-Soto et al, 2016;Lyu et al, 2019;Pavletić et al, 2022). Assay sensitivity would seem a likely explanation for these discrepancies.…”
Section: Discussionmentioning
confidence: 94%
“…In general, and providing further motivation for the present study, the particular role of β-arrestin at the D 4 receptor is still largely unclear. While some studies found that activation of the D 4 receptor by an agonist does not elicit β-arrestin recruitment or receptor internalization, other studies could well detect recruitment and desensitization. ,, In addition, the precise interplay of GRK2 and β-arrestin was shown to be of importance. , …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the structural background of bias between G protein and β-arrestin pathways, interactions of the functionally selective ligands with the ECL2 have been described to be a major factor. , In line with these findings, Wang et al postulated that the functional selectivity of 2 at the D 4 receptor stems from an interaction between the ligand’s quinolone moiety and the Leu-187 residue in ECL2. Ligand 4 , in addition to a interaction with Leu-187, also binds in proximity to the adjacent residues Cys-185 and Arg-186, thus resulting in antagonism at the β-arrestin pathway . An interaction at a proximate site (Val-184 and Arg-186) can be observed for APH199 ( 5 ) and its closely related derivatives, resulting in partial agonism at the β-arrestin pathway with bias factors up to 26 when compared to quinpirole …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials and general methods for the synthesis and chemical characterization of the final compounds and intermediates are reported in the ‘ Supplementary Materials ’ and given in references [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%